AKTIVITAS ANTIINFLAMASI EKSTRAK ETER KULIT BATANG TENGGULUN (Protium javanicum Burm) TERHADAP EDEMA PADA TIKUS WISTAR YANG DIINDUKSI DENGAN KARAGENAN - A. A. Tia Santika Dewi; Ni Made Puspawati; Putu Suarya (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
Stem bark of Tenggulun (Protium javanicum, Burm) has been used traditionally by Balinese people as anti-inflammatory agents. This research aimed to analyze phytochemical contents and to evaluate anti-inflammatory activity of stem bark ether extract of Tenggulun. Phytochemical study was done qualitatively using phytochemical reagents. Anti-inflammatory activity was evaluated on edema rats induced by carrageenan with given extract at doses of 125, 250, and 500 mg/kg b.w. Diclophenac sodium was used as the positive control. Phytochemical study revealed that the stem bark ether extracts consisted of alkaloids, steroids, terpenoids, and phenolic compounds. Anti-inflammatory activity test results showed at a dose of 125 mg/kg b.w, the extract only inhibit inflammation by 34.54%, while a dose of 250 mg/kg b.w gave inhibition of inflammation by 94.34%, and a dose of 500 mg/kg b.w can inhibit inflammation by 96.11% during 360 minutes observation. Probit analysis gave ED50 value of 103.252 mg/kg B.W.